(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Ivanissevich’s procedure is commonly practiced. However it was observed that the complication rate seen in this procedure was quite high then other techniques like Paloma or with laparoscopy.. Objective: We conducted this study to high light complication rate observed in Ivanissevich”s Procedure and discourage this procedure for varicocele treatment. Methodology: We conducted this study in surgical department of SIR GANGA RAM HOSPITAL LAHORE and 120 patients were included in it, over a period of two years from march 2014 to feb 2016.All the patients selected were having Left Sided Varicocele and we follow up these patients over the period of 6 months. C Results: Over a period of two years, 102 patients were operated (Ivanissevich”s procedure) for grade II Varicocele .there age ranges between 13 to 45 years with mean of 25.5 years.13patients (13%) developed scrotal edema which settled within ten days, post-operative hematomas observed in 6 patients(6%) and recurrence was the most common complication which was seen in 17 patients(17%).only one patient had testicular atrophy. Conclusion: Ivanissevich’s procedure has considerable complications then other available procedures like Paloma and Larorscopic Varicocelectomy